Developmental and comparative transcriptomic identification of iridophore contribution to white barring in clownfish. (29th January 2019) - Salis, Pauline; Lorin, Thibault; Lewis, Victor; Rey, Carine; Marcionetti, Anna; Escande, Marie‐Line; Roux, Natacha; Besseau, Laurence; Salamin, Nicolas; Sémon, Marie; Parichy, David; Volff, Jean‐Nicolas; et al.
Abstract: Actinopterygian fishes harbor at least eight distinct pigment cell types, leading to a fascinating diversity of colors. Among this diversity, the cellular origin of the white color appears to be linked to several pigment cell types such as iridophores or leucophores. We used the clownfish Amphiprion ocellaris, which has a color pattern consisting of white bars over a darker body, to characterize the pigment cells that underlie the white hue. We observe by electron microscopy that cells in white bars are similar to iridophores. In addition, the transcriptomic signature of clownfish white bars exhibits similarities with that of zebrafish iridophores. We further show by pharmacological treatments that these cells are necessary for the white color. Among the top differentially expressed genes in white skin, we identified several genes ( fhl2a, fhl2b, saiyan, gpnmb, and apoD1a ) and show that three of them are expressed in iridophores. Finally, we show by CRISPR/Cas9 mutagenesis that these genes are critical for iridophore development in zebrafish. Our analyses provide clues to the genomic underpinning of color diversity and allow identification of new iridophore genes in fish.